Fabrication of High-Density Polyethylene Matrix Surface Composite Reinforced by Various Powder Materials through Friction Stir Processing - Abdulbasit Abdulqadir Hamza; Shawnam Rashied Jalal (Zanco Journal of Pure and Applied Sciences, 2025)
Friction Stir Processing (FSP) is a promising technique to improve the surface properties of materials. Compared to metals, the FSP of polymeric materials was less studied. Therefore, in the present work, high-density polyethylene (HDPE) surface composite was fabricated by the addition of reinforcements such as Graphene (C), Silicon carbide (SiC), Silicon dioxide (SiO2), and Copper (Cu) powders. The effect of FSP parameters such as tool rotational speed (478, 679, and 925) rpm, traverse speed (22, 37, and 51) mm/min, and amount of added particles (10, 15, and 20) % on the mechanical properties of the fabricated samples were studied. The results showed that as the reinforcement powders were added to the matrix material, led to enhancements in each of the tensile strength, microhardness, and impact strength. At the optimum set of process parameters, the graphene-reinforced composites have better improvement in terms of tensile and impact strength where increased by (47.2 and 55.6) % respectively. On the other hand, in terms of microhardness, the SiC-reinforced composite exhibited greater augmentation, registering 20.16 %. While, the elongation of all fabricated composites decreased in comparison to the parent material. Based on the table of analysis of variance (ANOVA), it is noticed that the tool rotational speed has the largest effect on the quality of the products among the other parameters, followed by tool traverse speed and the amount of particles has the least contribution and effect. Considering the information provided, the friction stir process method can be used to repair cracks and other defects in polymeric materials.